Can Bugis-Makassar Local Culture Reduce Compulsive Buying Behavior? - Karim, Kasnaeny; Dani, Ibrahim (Hasanuddin Economics and Business Review, 2022)
This study aims to determine whether the local wisdom of Bugis culture is able to minimize consumer behavior in purchasing products, considering the negative impact caused by excessive shopping behavior with the use of credit cards that exceed the limit of funds or without the use of credit cards. Research informants amounted to 100 people obtained through snowball sampling. Research data were collected through open and closed questionnaires and interviews, then the research instrument was tested through validity and reliability tests using triangulation and peer review methods. The research method uses a narrative qualitative approach to obtain an explanation of whether the local wisdom of Bugis culture, namely "Siri'", is able to prevent compulsive buying behavior (consumerism). The results of the analysis show that siri' is believed to be able to prevent someone from spending excessively, because (1) there is a sense of shame to Self and Family, (2) There is shame to God Almighty, because God does not like people to do excessive behavior, and (3) there is a sense of shame about social sanctions when unable to pay arrears due to excessive use of credit cards.The implications of the results of this study can be used as reference material in preventing compulsive buying behavior and consumerism